Medium Matters: A Decade of Media Consumption Predicts Positive and Negative Dimensions of Self-Perceptions of Aging. (30th December 2020) - Boeder, Jordan; Tse, Dwight C K; Fruiht, Veronica; Chan, Thomas
Abstract: Objectives: Media consumption over time is suggested to be a significant contributor to how people develop their self-perceptions of aging (SPA); however, this association has only been investigated with cross-sectional methodologies. The current study used growth curve modeling to examine the influence of 10 years of television, newspaper, radio, and book consumption on positive and negative dimensions of SPA. Methods: Growth curve modeling on 4 waves of data from the German Aging Survey ( N = 2, 969), a population-based representative survey of adults aged 40–95, was used to examine the longitudinal associations between media consumption and SPA trajectories. Results: Across 10 years, more television intake ( B = −0.58, 95% CI [−0.94, −0.21]) was associated with lower perceptions of continuous growth. Inversely, greater book ( B = 0.10, 95% CI [0.06, 0.13]) and radio ( B = 0.52, 95% CI [0.29, 0.74]) consumption was significantly linked to higher perceptions of continuous growth. In parallel, more television ( B = 0.88, 95% CI [0.52, 1.25]) and newspaper consumption ( B = 0.46, 95% CI [0.04, 0.88]) was associated with higher perceptions of physical decline, while greater radio ( B = −0.40, 95% CI [−0.64, −0.16]) and book ( B = −0.05, 95% CI [−0.09, −0.00]) consumption was associated with lower perceptions of physical decline. Discussion: This study provides longitudinal evidence for the relationship between media consumption and SPA. However, not all types of media intake are negative as radio and book consumption were associated with better SPA across time. Age-group differences were investigated and are discussed in the Supplementary Materials .